2017
DOI: 10.1038/s41541-017-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Protein nanovaccine confers robust immunity against Toxoplasma

Abstract: We designed and produced a self-assembling protein nanoparticle. This self-assembling protein nanoparticle contains five CD8+ HLA-A03-11 supertypes-restricted epitopes from antigens expressed during Toxoplasma gondii’s lifecycle, the universal CD4+ T cell epitope PADRE, and flagellin as a scaffold and TLR5 agonist. These CD8+ T cell epitopes were separated by N/KAAA spacers and optimized for proteasomal cleavage. Self-assembling protein nanoparticle adjuvanted with TLR4 ligand-emulsion GLA-SE were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…SAPNs are based on coiled-coil domains and are traditionally expressed in Escherichia coli 8 . SAPN vaccine candidates have been developed for a variety of diseases such as malaria, SARS, influenza, toxoplasmosis, and HIV-1 9,10,11,12,13,14,15,16,17,18,19 . The design of each SAPN candidate is specific to the pathogen of interest, however, the production, purification, and refolding techniques are generally broadly applicable.…”
Section: Introductionmentioning
confidence: 99%
“…SAPNs are based on coiled-coil domains and are traditionally expressed in Escherichia coli 8 . SAPN vaccine candidates have been developed for a variety of diseases such as malaria, SARS, influenza, toxoplasmosis, and HIV-1 9,10,11,12,13,14,15,16,17,18,19 . The design of each SAPN candidate is specific to the pathogen of interest, however, the production, purification, and refolding techniques are generally broadly applicable.…”
Section: Introductionmentioning
confidence: 99%
“…Antigens and adjuvants can be inserted depending on the expected structure from in silico modeling [71] . Subunit malaria [72] , HIV [73] , toxoplasma [74] and severe acute respiratory syndrome [75] . Wahome et al, encapsulated two HIV protein epitopes (4E10 and 2F5) onto SAPN surface and observed enhanced production of epitope-specific neutralizing antibodies.…”
Section: Protein/peptide-based Nanovaccinesmentioning
confidence: 99%
“…A promising alternative delivery system for subunitbased vaccines has been developed recently [134] and used with vaccine candidates against several infectious diseases such as HIV [142], toxoplasma [143][144][145], SARS [146], influenza [147] and/or malaria [148][149][150]. The technique is known as Self-Assembling Protein Nanoparticles (SAPNs) and involves the expression of a peptide/ protein containing a target antigen covalently linked to an adjuvant sequence (flagellin-derived) and, in some cases, a universal epitope such as the Pan-DR T-helper epitope (PADRE) sequence.…”
Section: Future Directionsmentioning
confidence: 99%